Law and Economics of Obligations - Urs Schweizer (University of Bonn, Bonn Graduate School of Economics (BGSE), 2004)
While various liability rules of tort law provide efficient incentives to invest, breach remedies of contract law are claimed to be distortive. Since, at least in Germany, obligations law provides general rules for both contractual and tort relationships such discrepancy seems puzzling. The paper identifies a saddle point property as the driving force behind most efficiency results and it establishes that fault rules of a general type generate this property. The model is then confronted with important legal rules of the German law of obligations. The alleged inefficiency of expectation damages turns out to rest, not on a failure of breach remedies, but on the binary nature of delivery choice as imposed by the traditional analysis of contract law.
Keywords: K12; K13; D62; 330; Schuldrecht; Vertragsrecht; Haftung; Rechtsökonomik; Theorie